Influence of 2-(18F) Fluoro-2-Deoxy-d-Glucose Positron Emission Tomography/Computed Tomography on Recurrent Ovarian Cancer Diagnosis and on Selection of Patients for Secondary Cytoreductive Surgery. Issue 4 (1st April 2009) - Risum, Signe; Høgdall, Claus; Markova, Elena; Berthelsen, Anne K.; Loft, Annika; Jensen, Flemming; Høgdall, Estrid; Roed, Henrik; Engelholm, Svend A.
Abstract : The objective of this prospective study was to compare the sensitivities and the specificities of combined 2-( 18 F) fluoro-2-deoxy-d-glucose positron emission tomography/computed tomography (PET/CT), abdominal/transvaginal ultrasound (US), and CT for diagnosing recurrent ovarian cancer (OC) and to evaluate the influence of PET/CT on referral of patients with solitary recurrence to secondary cytoreductive surgery. From April 2005 to November 2007, 60 patients were consecutively included to PET/CT 68 times. The inclusion criteria were remission of 3 months or longer and recurrent OC suspected from physical examination, US, or increasing cancer antigen 125 (CA125) level (>50 U/mL or >15% above baseline level). Recurrent OC was diagnosed 58 times in 52 patients. The sensitivities of US, CT, and PET/CT for diagnosing recurrence were 66% ( P = 0.003), 81% ( P = 0.0001), and 97% ( P < 0.0001), respectively. The specificity of US, CT, and PET/CT for diagnosing recurrence was 90%. Positron emission tomography/CT diagnosed recurrence in 19 (66%) of 29 patients without recurrence according to US and in 10 (50%) of 20 patients without recurrence after CT. Multiple recurrent tumors were found using PET/CT in 27 (69%) of 39 patients with solitary tumors on US and in 8 (42%) of 19 patients with solitary tumors on CT. We conclude that the diagnostic value of PET/CT for detecting recurrent OC was higher than those of US and CT and that PET/CT more accurately identified patients with solitary recurrence. However, prospective clinical trials are needed to specify the characteristics of patients most likely to undergo complete secondary surgery and to further clarify the role of PET/CT in selecting patients for secondary surgery.